Does the "learning effect" caused by digital devices exaggerate sports visual training outcomes? a systematic review and meta-analysis - Guo, Y.; Yuan, T.; Yang, M.; Qiu, J. (Frontiers in Physiology, 2025)
Objective: Digital-based visual training (VT) is widely employed to improve visual-cognitive performance, yet its efficacy may be confounded by the "learning effect".